Management of adhesive intestinal obstruction - Niyaf, A; Bhandari, RS; Singh, KP (Journal of Institute of Medicine Nepal, 2011)
Introduction: Adhesive intestinal obstruction is an inevitable complication of abdominal surgeries. It has high morbidity with associated poor quality of life and predisposition to repeated hospitalization. Commonest cause of bowel obstruction in developed countries is postoperative adhesions with extrinsic compression of the intestine. Most of them can be managed conservatively. Methods: A retrospective study of 30 patients admitted with the diagnosis of post operative adhesive partial bowel obstruction was conducted by analyzing their medical records. Demographic data, clinical presentation including duration, previous surgical procedures, treatments received for the condition and successful conservative approach versus requirement of operative intervention were assessed. Results: The median age was 31 yrs, most in their third decade of life. Male predominance was noted. Pelvic surgeries and gynecological surgeries (26%) were found to be the most common cause of adhesive bowel obstruction followed by appendectomy (16%). More than two third of the patients (76.7%) developed symptoms within two years of the initial surgery. Successful conservative treatment was noted in 22 patients (73.3%) and discharged on fourth day of admission. Eight patients (26.6%) underwent surgery. They all underwent adhesiolysis and had good outcome. Conclusions: The time-honored practice of expectant management of adhesive partial bowel obstruction has equally good outcome, as compared to various interventions practiced Keywords: Adhesive bowel obstruction; conservative management DOI: http://dx.doi.org/10.3126/joim.v32i2.4939 Journal of Institute of Medicine, August, 2010; 32: 18-20